2020
DOI: 10.1101/2020.11.25.397836
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deciphering the LRRK code: LRRK1 and LRRK2 phosphorylate distinct Rab proteins and are regulated by diverse mechanisms

Abstract: Much attention has focused on LRRK2, as autosomal dominant missense mutations that enhance its kinase activity cause inherited Parkinson’s disease. LRRK2 regulates biology by phosphorylating a subset of Rab GTPases including Rab8A and Rab10 within its effector binding motif. In this study we explore whether LRRK1, a less studied homologue of LRRK2 that regulates growth factor receptor trafficking and osteoclast biology might also phosphorylate Rab proteins. Using mass spectrometry, we found that the endogenous… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 71 publications
0
28
0
Order By: Relevance
“…The late endosome marker Rab7 is phosphorylated by LRRK1, but not LRRK2, at S72. 73 Rab7 phosphorylation by LRRK1 has been implicated in mediating the recruitment of Rab7-interacting lysosomal protein (RILP), 74 a scaffold protein that promotes retrograde transport of late endosomes/lysosomes by enhancing dynein activity. 75 Previous work has shown that efficient autophagosomal cargo degradation is dependent on functional retrograde transport.…”
Section: Articlementioning
confidence: 99%
“…The late endosome marker Rab7 is phosphorylated by LRRK1, but not LRRK2, at S72. 73 Rab7 phosphorylation by LRRK1 has been implicated in mediating the recruitment of Rab7-interacting lysosomal protein (RILP), 74 a scaffold protein that promotes retrograde transport of late endosomes/lysosomes by enhancing dynein activity. 75 Previous work has shown that efficient autophagosomal cargo degradation is dependent on functional retrograde transport.…”
Section: Articlementioning
confidence: 99%
“…The functions of LRRK2 and its paralog LRRK1 are not fully understood. However, it is clear that a subset of Rab small GTPases (e.g., Rab8A and Rab10) are physiological substrates of LRRK2 [25] and are distinct from those that are phosphorylated by LRRK1 [26]. Only a subset of LRRK2 substrates, including Rab GTPases, have been validated in endogenous expression systems [25,27].…”
Section: Lrrk2: Substrates and Kinase Regulationmentioning
confidence: 99%
“…Between LRK-1 and LRRK1, there is a 20.9% amino acid identity (35.9% similarity), while between LRK-1 and LRRK2, there is a 20.3% identity (36.3% similarity) (118,138). LRRK1 and LRRK2 phosphorylate distinct subsets of RAB proteins, downstream effectors of LRRK activity (139), and mutations of LRRK1 lead to a rare bone condition, osteosclerotic metaphyseal dysplasia (140)(141)(142), also indicative of divergent functionality. Future modelling of key PD pathogenic LRRK2 mutations and variants in C. elegans LRK-1 (Figure 4), may shed light on the extent of functional conservation between C. elegans LRK-1 and mammalian LRRK1 and LRRK2.…”
Section: The Evolutionary Conservation Of Lrrk2 In C Elegansmentioning
confidence: 99%